2012
DOI: 10.3109/10409238.2012.667214
|View full text |Cite
|
Sign up to set email alerts
|

Ccr4-Not complex: the control freak of eukaryotic cells

Abstract: The purpose of this review is to provide an analysis of the latest developments on the functions of the Ccr4-Not complex in regulating eukaryotic gene expression. Ccr4-Not is a nine-subunit protein complex that is conserved in sequence and function throughout the eukaryotic kingdom. Although Ccr4-Not has been studied since the 1980s, our understanding of what it does is constantly evolving. Once thought to solely regulate transcription, it is now clear that it has much broader roles in gene regulation, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
199
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(204 citation statements)
references
References 167 publications
(315 reference statements)
4
199
1
Order By: Relevance
“…In this case, transcript-specific targeting of CNOT2 would rely combinatorially on its promoter-specific recruitment by TFs and RBP-dependent loading onto the transcribing mRNA. It is also notable that the coordinated functions of CCR4-NOT in transcription and mRNA decay rely more specifically on its NOT2-NOT3 module, which interacts with ERG 11 .…”
Section: Discussionmentioning
confidence: 99%
“…In this case, transcript-specific targeting of CNOT2 would rely combinatorially on its promoter-specific recruitment by TFs and RBP-dependent loading onto the transcribing mRNA. It is also notable that the coordinated functions of CCR4-NOT in transcription and mRNA decay rely more specifically on its NOT2-NOT3 module, which interacts with ERG 11 .…”
Section: Discussionmentioning
confidence: 99%
“…This process is carried out by Pan2/3 and Ccr4 in yeast, with Ccr4 appearing to play the major role (9 -11). Ccr4 resides in a multisubunit complex called Ccr4-Not, which was first described as a transcriptional activator/ repressor (9,12). In addition to regulating the TATA-binding protein at the initiation stage, it directly associates with elongating RNA polymerase II (RNAPII) 2 and can reactivate arrested polymerase in vitro (13,14).…”
mentioning
confidence: 99%
“…The mammalian CCR4-NOT complex consists of multiple modules involved in transcription (CNOT2/ CNOT3), mRNA degradation (CNOT6/CNOT6L/ CNOT7/CNOT8), and protein quality control (CNOT4) (for review, see Miller and Reese 2012). We found that EBF1 interacts specifically with the CNOT3 subunit of the complex.…”
Section: Discussionmentioning
confidence: 93%
“…The CCR4-NOT complex is assembled around the CNOT1 subunit, which serves as a scaffold and interacts with various modules. The CNOT2 and CNOT3 subunits together form a module engaged in gene transcription and RNA targeting, whereas CNOT6, CNOT6L, CNOT7, and CNOT8 form a "deadenylase module" involved in mRNA degradation (for review, see Miller and Reese 2012;Collart et al 2013). In addition, CNOT4 represents a module for protein quality control that is not a constitutive component of the complex (Lau et al 2009;Bhaskar et al 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation